2012
DOI: 10.4040/jkan.2012.42.4.508
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology on the Lived Experience of Korean Women with Spinal Cord Injuries

Abstract: Purpose: The purpose of the study was to understand and explain the essences and structures of the experience of Korean women who have had a spinal cord injury. Methods: The data were collected in 2010 through individual in-depth interviews using open-ended questions. A total of 9 women with spinal cord injuries participated in the study. Each interview lasted about 2 hours. Verbatim transcripts were analyzed using phenomenological analysis. Results: Five theme clusters emerged from the analysis using Colaizzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Gender roles have been analyzed qualitatively in women with acquired disabilities. Hwang, Yi, Park, and Kwon () found that women who had recently sustained SCI felt shame and helplessness concerning their paralyzed bodies, were concerned about their roles as wives or mothers, and experienced guilt regarding their husbands, children, or parents. In addition, some participants expressed conflict between adjustment and acceptance, confronted disadvantage resulting from their disabilities, and felt as though they had been reborn.…”
Section: Main Studies Conducted In Korea and Chinamentioning
confidence: 99%
“…Gender roles have been analyzed qualitatively in women with acquired disabilities. Hwang, Yi, Park, and Kwon () found that women who had recently sustained SCI felt shame and helplessness concerning their paralyzed bodies, were concerned about their roles as wives or mothers, and experienced guilt regarding their husbands, children, or parents. In addition, some participants expressed conflict between adjustment and acceptance, confronted disadvantage resulting from their disabilities, and felt as though they had been reborn.…”
Section: Main Studies Conducted In Korea and Chinamentioning
confidence: 99%